2020
DOI: 10.25046/aj050250
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Analysis of Usability and Learning Methods on an Augmented Reality Application for Zoology Education

Abstract: In recent years, research has been conducted focused on the use of technologies in the classroom, but one of the main problems is to demonstrate that the use of this technology favors learning compared to traditional methods. One of these technologies is augmented reality that allows seeing virtual objects superimposed in the real world, but to achieve its correct use it is necessary to evaluate the usability that is the ease with which an interface is used. In this work we develop and analyze from two perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…However, it is important to apply appropriate design methods (Rohaya et al, 2012), development approaches (Abrar et al, 2019), and usability principles (Tuli & Mantri, 2020) when creating augmented reality educational resources. Well-designed augmented reality interventions can positively affect students' cognitive mechanisms, increase their focus on the learning activities, encourage them to reflect and revise the learning material, and provide them with opportunities to apply what they learn (Campos-Pajuelo et al, 2022;Iquira-Becerra et al, 2020;Oranc ¸& Küntay, 2019). When augmented reality applications are integrated into preschool and primary education, increased interaction and engagement with the material which, in turn, results in improved academic performance can be observed, even if students are not initially familiar with the technology (Abrar et al, 2019;Campos-Pajuelo et al, 2022;Safar et al, 2016;Stoyanova et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to apply appropriate design methods (Rohaya et al, 2012), development approaches (Abrar et al, 2019), and usability principles (Tuli & Mantri, 2020) when creating augmented reality educational resources. Well-designed augmented reality interventions can positively affect students' cognitive mechanisms, increase their focus on the learning activities, encourage them to reflect and revise the learning material, and provide them with opportunities to apply what they learn (Campos-Pajuelo et al, 2022;Iquira-Becerra et al, 2020;Oranc ¸& Küntay, 2019). When augmented reality applications are integrated into preschool and primary education, increased interaction and engagement with the material which, in turn, results in improved academic performance can be observed, even if students are not initially familiar with the technology (Abrar et al, 2019;Campos-Pajuelo et al, 2022;Safar et al, 2016;Stoyanova et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Research of AR applications covers many different use cases and industries. One study has uncovered findings such as children seem to understand how to use the augmented reality application as soon as they began to interact with the technology [4]. Another research effort found learning English utilizing AR can help students in learning material and motivated students to learn the language [5].…”
Section: Introductionmentioning
confidence: 99%